Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. Performance of yearling beef heifers fed various ratios of sorghum grain to dehydrated alfalfa in pellet form. - Smith, E.F.; Koch, B.A.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the first year of an experiment designed to investigate the value of a complete pelleted ration for fattening cattle. Since Kansas has an abundance of sorghum grain and alfalfa, the 1960 study was designed to study the performance of yearling heifers fed various ratios of sorghum grain to dehydrated alfalfa in pellet form. Dehydrated alfalfa served as a source of roughage and protein.
Keywords: Beef; Roughages; Curing; Performance; Sorghum grain; Dehydrated alfalfa